Legal Analysis Officers Land Deed and Notary Which Different Place Position - Afdal Batara Agung (Faculty of Law, University of Mataram, 2017)
This study aims to analyze how to regulate the placement of PPAT in Government Regulation No. 24 of 2016 on the Amendment of Government Regulation Number 37 of 1998 on the Regulation of Officials of the Land Deed Authority and the factors that affect the occurrence of different working areas of PPAT and Notary positions. This research is done by using normative-empirical research method with data collecting technique through interview that is direct dialog in the form of question and answer and document study that is by recording data directly from document which its contents related to research problem, that is rule of law, , papers, journals, seminar results, and internet sites. The results of this study indicate that: 1) The working area of ​​PPAT in PP 24/2016 is expanded into provincial work areas. in relation to the working area of ​​PPAT in PP 24/2016 provides confirmation that PPAT and Notary are required to be within a working area if it is understood that PPAT in this case concurrently serves as a Notary. In the provision of Article 9 Paragraph (1) of PP 24/2016, PPAT in having two options, such option is PPAT filed a request to move the seat of PPAT or other option of PPAT must stop as Notary in its place of domicile. 2) the age of 22 years can be appointed to PPAT will potentially make the existence of different office positions between PPAT and notary since PPAT first open the office from the notary. PPAT concurrently holds the position of notary but does not follow the notary's position on violating the provisions of Article 7 paragraph (2) letter h of PP 24/2016 and Article 17 letter g UUJN.